(3HOGFY GdRghQ aj hbGFY GdOghQs - (3eMeO Hf CMeO Hf EjGS GdMfaj GdeUQj, CHh GdHQcGJ,J (B930 (3g` s
(3ChdgG (B:s
(3PcQ GHJOGA OhdI GdLQGcSI HeUQ s
(3BNQgG (B:s
(3hcGf GdaQGZ ef gPg GdfSNI Ydi jOcGJHgG heDdagG eMeO Hf CMeO GHf EjGS GdMfaj hPdc aj jhe GdNejS KGfj QLH GdaQO dSfI CQHY JSYeGFI s
(3GfXQ Qbe (B78s
(3Qbe (B924 (3JGQjNs
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs